Evaluation of Vitamin D3 serum as biomarker of metabolic activity and body composition in a study sample - Nicosia, Danilo; Centofanti, Domenico; Galluccio, Angelo; Pecorella, Claudio; Bartoletti, Emanuele (Aesthetic Medicine, 2026)
Background: Vitamin D has an important function on regulating calcium-phosphorus metabolism. It is involved in multiple extra-skeletal processes and supports physiological and metabolic functions. Aim: to investigate the association between vitamin D levels and the lipid profile. Material and Methods: Through a cross-sectional retrospective analysis, the participants underwent different assessments, in order to identify the possible correlations between vitamin D levels and changes in clinical, metabolic, and body parameters. Given the cross-sectional and retrospective nature of the study, observed associations should not be interpreted as causal, but rather as potential correlational findings warranting further prospective investigation. Results: A correlation emerged between vitamin D levels and serum triglyceride concentration in women, with lower triglycerides observed in women with average (p=0.028) and optimal (p=0.036) vitamin D levels. Conclusions: These exploratory findings suggest a potential correlational role for vitamin D in lipid assessment, warranting further study.